PI(4,5)P2-dependent and -independent roles of PI4P in the control of hormone secretion by pituitary cells - Stojilkovic, Stanko S.; Balla, Tamas (Frontiers in Endocrinology, 2023)
Plasma membrane and organelle membranes are home to seven phosphoinositides, an important class of low-abundance anionic signaling lipids that contribute to cellular functions by recruiting cytoplasmic proteins or interacting with the cytoplasmic domains of membrane proteins. Here, we briefly review the functions of three phosphoinositides, PI4P, PI(4,5)P2, and PI(3,4,5)P3, in cellular signaling and exocytosis, focusing on hormone-producing pituitary cells. PI(4,5)P2, acting as a substrate for phospholipase C, plays a key role in the control of pituitary cell functions, including hormone synthesis and secretion. PI(4,5)P2 also acts as a substrate for class I PI3-kinases, leading to the generation of two intracellular messengers, PI(3,4,5)P3 and PI(3,4)P2, which act through their intracellular effectors, including Akt. PI(4,5)P2 can also influence the release of pituitary hormones acting as an intact lipid to regulate ion channel gating and concomitant calcium signaling, as well as the exocytic pathway. Recent findings also show that PI4P is not only a precursor of PI(4,5)P2, but also a key signaling molecule in many cell types, including pituitary cells, where it controls hormone secretion in a PI(4,5)P2-independent manner.